Answer: First option
Step-by-step explanation:
You have the quadratic equation given in the problem:
![m^2-13m-30](https://tex.z-dn.net/?f=m%5E2-13m-30)
To find an equivalent expression you cacn factorize. Find two numbers whose sum is -13 and whose product is -30.
These numbers would be -15 and 2.
Therfore, you obtain the following equivalent expression:
![(m-15)(m+2)](https://tex.z-dn.net/?f=%28m-15%29%28m%2B2%29)
If you don't want to apply the method above, you can use the quadratic formula:
![x=\frac{-b+/-\sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-b%2B%2F-%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D)
Where:
![a=1\\b=-13\\c=-30](https://tex.z-dn.net/?f=a%3D1%5C%5Cb%3D-13%5C%5Cc%3D-30)
When you susbstitute values you obtain that:
![x=15\\x=-2](https://tex.z-dn.net/?f=x%3D15%5C%5Cx%3D-2)
Then you can rewrite the equation as ![(m-15)(m+2)](https://tex.z-dn.net/?f=%28m-15%29%28m%2B2%29)